Learning to coach: An ecological dynamics perspective - Wood, M. A.; Mellalieu, S. D.; Araújo, D.; Woods, C. T.; Davids, K. (International Journal of Sports Science & Coaching, 2023)
A constraints-led approach (CLA), based on an ecological dynamics rationale for athlete learning and development has been applied to analyses of individual and team sports. To date, such an approach has yet to be applied to the learning of coaches. Here, we propose how applying a CLA in education and professional development programmes can shape emerging behaviours of coaches as they interact with constraints of representative environments to adapt their practice. A core concept within ecological dynamics for coach education is the conceptual differentiation between knowledge of (direct perception) and knowledge about (indirect perception) the environment. Current coach education and development practices focus primarily on the acquisition and transmission of knowledge about, which over-relies on provision of (abstract) verbal and visual augmented corrective information found in manuals. Reconsidering coaches` behaviours as emerging under constraints provides a coach developer opportunities to identify and manipulate key individual, environmental and task constraints. This approach guides attention to relevant and alternative affordances (opportunities for action) when coaching, and promotes continuous self-regulation of coach learning, supported by an experienced mentor. Learning to coach through a CLA could result in an extensive appreciation of multiple sources of knowledge, resulting in a continuously deepening fit between the coach and their performance environment. An ecological perspective of a coach learning to adapt to the constraints of a performance environment offers an alternative to current formalised coach development practice.